Forming method of petroleum coke powder coke and formed coke
After screening and mixing petroleum coke powder, it is pressed and calcined on the molding machine, which solves the problems of high forming pressure, high equipment requirements and pollution in the existing technology, and realizes low-pressure and low-energy consumption coke molding, which improves the strength and industrial application potential of coke.
Patent Information
- Application Number
- CN202411766236.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-14
AI Technical Summary
The existing petroleum coke powder coke molding technology has problems such as high forming pressure, high equipment requirements, many binder impurities, complex molding process and pollution, and has not been industrially applied in the production of pre-baked anodes.
After using a screen to make powder coke, asphalt binder, non-asphalt binder and water containing surfactant are added, and after stirring evenly, the molding is pressed on the molding machine to form a coke raw material and calcinate it to achieve molding of the coke.
It achieves low molding pressure, low equipment requirements, and low binder impurities content. The molding process is carried out at room temperature, avoiding asphalt smoke pollution during heating, and the prepared coke raw blocks and calcined cokes have high strength, which can directly treat moisture-containing powder cokes, reducing energy consumption and process flow.
Smart Images

Figure CN119613118A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of carbon materials, and in particular to a method for forming petroleum coke powder and shaped coke. Background Art
[0002] In recent years, the increase of petroleum coke powder has become a major problem that troubles prebaked anode companies. If petroleum coke with a large amount of powder is directly used for anode production, it will affect the material balance of the production process, causing fluctuations in the volume density, strength, resistivity and other indicators of the carbon anode, and then cause fluctuations in the aluminum electrolysis process; it will lead to a high calcination loss rate of petroleum coke, increase production costs, and increase carbon emissions during the calcination process; it is easy to "explode" during calcination in a pot calciner, affecting production safety; when calcining in a rotary kiln, the powder is in the lower layer of the rotary kiln material, making the calcination temperature of the powder low, and the true density of the calcined coke produced does not meet the requirements, affecting the anti-oxidation properties of the carbon anode and other indicators.
[0003] Coke powder forming technology is an effective way to solve the problem of large amounts of petroleum coke powder. However, previous studies on coke powder forming technology have problems such as high forming pressure, high equipment requirements, or the binder contains a lot of impurities, resulting in poor performance of the coke after forming, or heating is required during forming, which results in a complex process and pollution. Existing petroleum coke powder forming technology has not been industrialized in the production of prebaked anodes. Summary of the invention
[0004] The present disclosure aims to solve at least one of the technical problems existing in the prior art or related art.
[0005] To this end, a first aspect of the present disclosure provides a method for forming petroleum coke powder, comprising:
[0006] Screening of fine coke, screening petroleum coke to obtain fine coke;
[0007] Mixture preparation: adding an asphalt binder, a non-asphalt binder and water containing a surfactant to the powdered coke to obtain a mixture;
[0008] Pressing the mixture into a mold, pressing the mixture into a mold on a molding machine to obtain molded coke green blocks;
[0009] The molded coke block is calcined, and the molded coke green block is calcined to obtain molded coke.
[0010] In a feasible implementation, in the step of screening the coke powder, the particle size of the coke powder is less than or equal to 5 mm, the volatile matter of the coke powder is 7% to 13%, and the moisture content of the coke powder is 0.1% to 9%.
[0011] In one possible embodiment, the weight ratio of the asphalt binder to the dry basis coke is 0.03 to 0.13.
[0012] In a feasible implementation, the particle size of the asphalt binder is less than 2 mm, and the softening point of the asphalt binder is 90° C. to 150° C., and the coking value is 40% to 65%.
[0013] In a feasible implementation manner, the forming machine is configured as a double-roll forming machine, and the line pressure ratio of the double-roll forming machine is configured to be 0.2 to 1.5 t / cm.
[0014] In a feasible embodiment, the non-asphalt binder is guar gum, sesbania gum or hydroxypropyl methylcellulose.
[0015] In one possible embodiment, the weight ratio of the non-asphalt binder to the dry basis coke powder is 0.02 to 0.03.
[0016] In a feasible implementation manner, the water containing the surfactant and the original water in the coke powder constitute a total moisture content, and the weight ratio of the total moisture content to the dry basis coke powder is 0.10 to 0.14.
[0017] In a feasible embodiment, in the step of calcining the coke blocks, the temperature is set to 1100°C to 1300°C.
[0018] In a second aspect of the present disclosure, there is provided a shaped coke, which is made by the above-mentioned petroleum coke powder molding method.
[0019] Compared with the prior art, the present invention at least includes the following beneficial effects: the powder coke molding method of the present invention has a low molding pressure, can directly process powder coke containing water, the powder coke does not need to be dried, and has low equipment requirements; the impurity content of the binder and the molded coke is low; the mixing and molding process is carried out at room temperature, does not require heating, has low energy consumption, and can avoid the problem of asphalt fume pollution generated during heating; the prepared molded coke green blocks have high strength, are not easy to break during transportation and transfer, and have high strength after calcination; powder coke containing water can be directly processed without the need to dry the powder coke before processing, which further reduces energy consumption and shortens the process flow. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present disclosure and, together with the description, serve to explain the principles of the present disclosure.
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.
[0022] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the exemplary embodiments below. The accompanying drawings are only for the purpose of illustrating exemplary embodiments and are not to be considered as limiting the present application. Also, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0023] Figure 1 A schematic flow chart of a method for forming petroleum coke powder provided in the present invention. DETAILED DESCRIPTION
[0024] In order to more clearly understand the above-mentioned objectives, features and advantages of the present disclosure, the scheme of the present disclosure will be further described below. It should be noted that the embodiments of the present disclosure and the features in the embodiments can be combined with each other without conflict.
[0025] In the following description, many specific details are set forth to facilitate a full understanding of the present disclosure, but the present disclosure may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present disclosure, rather than all of the embodiments.
[0026] At present, the powder coke forming technology is an effective way to solve the problem of large amount of petroleum coke powder. However, the previous studies on the powder coke forming technology have problems such as high forming pressure, high equipment requirements, or the binder contains a lot of impurities, the performance of the coke after forming is poor, or the forming process requires heating, the process is complicated, and there is pollution. The existing petroleum coke powder forming technology has not been industrialized in the production of prebaked anodes.
[0027] Based on this, the embodiments of the present disclosure provide a method for forming petroleum coke powder. The powder coke forming method of the present disclosure has low forming pressure, can directly process powder coke containing moisture, the powder coke does not need to be dried, and has low equipment requirements; the impurity content of the binder and the mold coke is low; the mixing and forming process is carried out at room temperature, does not require heating, has low energy consumption, and can avoid the problem of asphalt fume pollution generated during heating; the prepared mold coke green block has high strength, is not easy to break during transportation and transfer, and has high strength after calcination; powder coke containing moisture can be directly processed without the need to dry the powder coke before processing, which further reduces energy consumption and shortens the process flow.
[0028] The forming method of the petroleum coke powder is described in detail below by means of specific embodiments:
[0029] like Figure 1 As shown, in a first aspect of the present disclosure, a method for forming petroleum coke powder is provided, comprising:
[0030] Screening of fine coke, screening petroleum coke to obtain fine coke; preparation of mixture, adding asphalt binder, non-asphalt binder and water containing surfactant to the fine coke, and stirring evenly to obtain a mixture; molding of the mixture, molding the mixture on a molding machine to obtain molded coke green blocks; calcining of molded coke blocks, calcining the molded coke green blocks to obtain molded coke.
[0031] The powder coke forming method disclosed in the present invention has low forming pressure and low equipment requirements, and can directly process powder coke containing water, and the powder coke does not need to be dried; the impurity content of the binder and the mold coke is low; the mixing and forming process is carried out at room temperature, no heating is required, the energy consumption is low, and the asphalt fume pollution problem generated during heating can be avoided; the prepared mold coke green block has high strength, is not easy to break during transportation and transfer, and the mold coke after calcination has high strength; the powder coke containing water can be directly processed without drying the powder coke before processing, which further reduces energy consumption and shortens the process flow. Specifically, asphalt binder, non-asphalt binder and water containing surfactant are added to the powder coke, and a kneading pot is used to stir evenly to obtain a mixture. Furthermore, stirring and pressing are carried out in an environment of 1 to 40°C, and the stirring and pressing processes are not heated. The addition of asphalt binder to the powder coke can ensure that the binder produces sufficient coking after calcination, so that a strong bonding force is formed between the powder coke particles, and the addition of non-asphalt binder to the powder coke is because it is necessary to use these binders that have a bonding effect at room temperature to make the mold coke green block have sufficient strength. The surfactant can be selected from one of Peregrine O-20, Peregrine O-25, and Peregrine O-30, wherein the weight ratio of the surfactant to water is 0.001 to 0.005. The above surfactant is easily soluble in water, and its aqueous solution can well wet the petroleum coke powder, asphalt binder and non-asphalt binder, has low cost, and will not increase the impurity element content of the coke.
[0032] In some embodiments, in the step of screening the powdered coke, the particle size of the powdered coke is less than or equal to 5 mm, the volatile matter of the powdered coke is 7% to 13%, and the moisture content of the powdered coke is 0.1% to 9%.
[0033] In this embodiment, the particle size of the powdered coke is not greater than 5 mm, because large-particle petroleum coke is used in prebaked anode production, and a series of problems caused by powdered coke will not occur. The volatile matter of the powdered coke is 7-13%, which is in line with the actual volatile matter of petroleum coke powdered coke, and a lower volatile matter will have an adverse effect on the strength of the calcined coke. Too high a volatile matter will make the porosity of the calcined coke too high, affecting the density of the coke. The moisture content of the powdered coke is 0.1% to 9%, which is in line with the actual situation, and too high a moisture content will make it difficult to screen the powdered coke.
[0034] In some embodiments, the weight ratio of asphalt binder to dry basis fine coke is from 0.03 to 0.13.
[0035] In this embodiment, the weight ratio of the asphalt binder to the dry-based coke powder is 0.03 to 0.13. Such a ratio is required to ensure the strength of the coke, and will not make the asphalt binder dosage too high, thereby causing excessive cost. It should be noted that the dry-based coke powder described in the present disclosure is the coke powder from which the water is removed from the petroleum coke powder.
[0036] In some embodiments, the particle size of the asphalt binder is less than 2 mm, and the softening point of the asphalt binder is 90° C. to 150° C., and the coking value is 40% to 65%.
[0037] In this embodiment, the asphalt binder has a softening point of 90°C to 150°C and a coking value of 40% to 65%. The above indicators can ensure that the asphalt binder can better wet the coke particles after melting during the calcination heating process, which is conducive to the final bonding effect. In addition, the asphalt binder can eventually produce more coke, so that the coke particles have a stronger bonding force. The particle size of the asphalt binder is less than 2mm, which can ensure that the asphalt binder is more fully mixed with other materials, and asphalt of this particle size is easy to prepare.
[0038] In some embodiments, the forming machine is configured as a double-roll forming machine, and a line pressure ratio of the double-roll forming machine is configured to be 0.2 to 1.5 t / cm.
[0039] In this embodiment, the double-roll forming machine is low in price and is used to prepare molded coke, with good forming effect and high efficiency. The linear pressure ratio of the double-roll forming machine is controlled between 0.2-1.5 t / cm, which can ensure that the molded coke lump and the calcined molded coke have high strength, and such a linear pressure ratio is easy to achieve and has low requirements on the molding equipment.
[0040] In some embodiments, the non-asphalt binder is guar gum or sesbania gum or hydroxypropyl methylcellulose. The above binders are relatively low in price, low in impurity content, and have good bonding effects.
[0041] In some embodiments, the weight ratio of the non-asphalt binder to the coke powder is 0.02 to 0.03. In this embodiment, the weight ratio of the non-asphalt binder to the dry basis coke powder is 0.02-0.03, which is required to ensure the strength of the green coke block without causing the non-asphalt binder to be used in excessive amounts, thereby resulting in excessive costs.
[0042] In some embodiments, the water containing the surfactant and the original water in the coke powder constitute the total water, and the weight ratio of the total water to the dry basis coke powder is 0.10 to 0.14.
[0043] In this embodiment, the water containing the surfactant and the original water in the powdered coke constitute the total water content, and the weight ratio of the total water content to the dry powdered coke is 0.10 to 0.14. The above ratio can ensure that there is enough water in the mixture, the mixture has good plasticity and molding effect, and the molded coke block has high strength; if the water content is too high, the mixture will become sticky, affecting the molding process, and a large amount of water will escape from the molded coke during calcination, resulting in more cracks.
[0044] In some embodiments, in the step of calcining the coke blocks, the temperature is set at 1100°C to 1300°C.
[0045] In this embodiment, the maximum temperature of the calcination process is 1100°C to 1300°C. After calcination, the true density of the coke is ≥2.03 g·cm -3 The above calcination process requirements can ensure the calcination degree of the coke, so that it meets the index requirements of calcined coke for prebaked anode. If the true density of the calcined coke is less than 2.03g·cm -3 , it will be treated as a defective product and mixed into petroleum coke or molded coke green blocks and re-calcined.
[0046] Drop strength is a method to measure the strength of green coke. The higher the drop strength, the higher the strength of the green coke. Particle stability is a method to measure the strength of calcined coke particles. The higher the particle stability, the higher the calcined coke particle strength. The particle stability of calcined petroleum coke is generally between 65% and 85%. In the following examples, drop strength is used to measure the strength of green coke, and particle stability is used to measure the strength of calcined coke.
[0047] Example 1
[0048] The coke powder is screened to obtain coke powder with a particle size of less than or equal to 4 mm, a volatile matter of 12.06%, and a moisture content of 6.37%.
[0049] Preparation of the mixture: adding asphalt binder, non-asphalt binder and water containing surfactant to the coke powder, using a kneading pot to stir evenly to obtain the mixture. Among them, the softening point of the asphalt binder is 118°C, the coking value is 58.07%, the particle size is less than 2 mm, and the weight ratio of the asphalt binder to the dry basis coke powder is 0.06; the non-asphalt binder is hydroxypropyl methylcellulose, and the weight ratio of the non-asphalt binder to the dry basis coke powder is 0.025; the water containing the surfactant and the original water in the coke powder constitute the total water, and the weight ratio of the total water to the dry basis coke powder is 0.13; the weight ratio of the surfactant to the water in the water containing the surfactant is 0.002, and the surfactant is Peregal O-20.
[0050] The mixed material is pressed on a double-roll forming machine with a linear pressure ratio of 0.8 t / cm. After pressing, a molded coke green block is obtained. The drop strength of the molded coke green block is 85.38%. The ambient temperature for stirring and pressing is 31°C.
[0051] The molded coke block is calcined. The molded coke green block is calcined at a maximum temperature of 1250°C to obtain molded coke. The true density of the molded coke is 2.06 g·cm -3 , particle stability is 71.76%, powder resistivity is 506μΩ·m, and ash content is 0.27%.
[0052] Example 2
[0053] The coke powder is screened to obtain coke powder with a particle size of less than or equal to 2 mm, a volatile matter of 9.25%, and a moisture content of 8.83%.
[0054] Preparation of the mixture: add asphalt binder, non-asphalt binder and water containing surfactant to the coke powder, use a kneading pot to stir evenly, and obtain a mixture. Among them, the softening point of the asphalt binder is 147°C, the coking value is 64.29%, the particle size is less than 2 mm, and the weight ratio of the asphalt binder to the dry basis coke powder is 0.13; the non-asphalt binder is a mixture of guar gum and sesbania gum in a weight ratio of 1:1, and the weight ratio of the non-asphalt binder to the dry basis coke powder is 0.02; the water containing surfactant and the original water in the coke powder constitute the total water, and the weight ratio of the total water to the dry basis coke powder is 0.12; the weight ratio of the surfactant to water in the water containing surfactant is 0.003, and the surfactant is Peregal O-30.
[0055] The mixed material is pressed on a roll forming machine with a linear pressure ratio of 1.2 t / cm to obtain a molded coke lump. The drop strength of the molded coke lump is 79.87%. The ambient temperature for stirring and pressing is 17°C.
[0056] Calcination of coke blocks: calcining coke blocks at a maximum temperature of 1300°C to obtain coke blocks. The true density of coke blocks is 2.07 g·cm -3 , particle stability is 79.31%, powder resistivity is 496μΩ·m, and ash content is 0.32%.
[0057] Example 3
[0058] The coke powder is screened to obtain coke powder with a particle size of less than or equal to 1 mm, a volatile matter of 7.24%, and a moisture content of 4.31%.
[0059] Preparation of the mixture: adding asphalt binder, non-asphalt binder and water containing surfactant to the coke powder, and stirring evenly in a kneading pot to obtain a mixture. Among them, the softening point of the asphalt binder is 116°C, the coking value is 56.61%, the particle size is less than 2 mm, and the weight ratio of the asphalt binder to the dry coke powder is 0.11; the non-asphalt binder is mixed with guar gum, sesbania gum and hydroxypropyl methylcellulose in a weight ratio of 1:1:1, and the weight ratio of the non-asphalt binder to the dry coke powder is 0.027; the water containing the surfactant and the original components in the coke powder constitute the total water, and the weight ratio of the total water to the dry coke powder is 0.12; the weight ratio of the surfactant to water in the water containing the surfactant is 0.001, and the surfactant is Peregal O-25.
[0060] The mixed material is pressed on a double-roll forming machine with a linear pressure ratio of 0.5 t / cm. After pressing, a molded coke green block is obtained. The drop strength of the molded coke green block is 81.95%. The ambient temperature for stirring and pressing is 14°C.
[0061] Calcination of coke blocks: calcining coke blocks at a maximum temperature of 1100°C to obtain coke blocks. The true density of coke blocks is 2.03 g·cm -3 , particle stability is 73.92%, powder resistivity is 551μΩ·m, and ash content is 0.36%.
[0062] Example 4
[0063] The coke powder is screened to obtain coke powder with a particle size of less than or equal to 5 mm, a volatile matter of 12.87%, and a moisture content of 0.19%.
[0064] Preparation of the mixture: adding asphalt binder, non-asphalt binder and water containing surfactant to the coke powder, using a kneading pot to stir evenly to obtain a mixture. Among them, the softening point of the asphalt binder is 101°C, the coking value is 53.29%, the particle size is less than 2 mm, and the weight ratio of the asphalt binder to the dry coke powder is 0.03; the non-asphalt binder is a mixture of guar gum and hydroxypropyl methylcellulose in a weight ratio of 1:1, and the weight ratio of the non-asphalt binder to the dry coke powder is 0.03; the water containing the surfactant and the original water in the coke powder constitute the total water, and the weight ratio of the total water to the dry coke powder is 0.10; the weight ratio of the surfactant to water in the water containing the surfactant is 0.005, and the surfactant is Peregal O-25.
[0065] The mixed material is pressed on a roll forming machine with a linear pressure ratio of 1.5 t / cm to obtain a molded coke lump. The drop strength of the molded coke lump is 84.29%. The ambient temperature for stirring and pressing is 38°C.
[0066] Calcination of coke blocks: calcining coke blocks at a maximum temperature of 1150°C to obtain coke blocks. The true density of coke blocks is 2.04 g·cm -3 , particle stability is 68.20%, powder resistivity is 534μΩ·m, and ash content is 0.25%.
[0067] Example 5
[0068] The coke powder is screened to obtain coke powder with a particle size of less than or equal to 4 mm, a volatile matter of 11.43%, and a moisture content of 8.74%.
[0069] Preparation of the mixture: adding asphalt binder, non-asphalt binder and water containing surfactant to the coke powder, and stirring evenly in a kneading pot to obtain the mixture. Among them, the softening point of the asphalt binder is 135°C, the coking value is 59.72%, the particle size is less than 2 mm, and the weight ratio of the asphalt binder to the dry basis coke powder is 0.08; the non-asphalt binder is guar gum, and the weight ratio of the non-asphalt binder to the dry basis coke powder is 0.027; the water containing the surfactant and the original water in the coke powder constitute the total water, and the weight ratio of the total water to the dry basis coke powder is 0.14; the weight ratio of the surfactant to the water in the water containing the surfactant is 0.002, and the surfactant is Peregal O-20.
[0070] The mixed material is pressed on a double-roll forming machine with a linear pressure ratio of 0.8 t / cm. After pressing, a molded coke green block is obtained. The drop strength of the molded coke green block is 90.21%. The ambient temperature for stirring and pressing is 19°C.
[0071] The molded coke block is calcined. The molded coke green block is calcined at a maximum temperature of 1250°C to obtain molded coke. The true density of the molded coke is 2.07 g·cm -3 , particle stability is 76.79%, powder resistivity is 508μΩ·m, and ash content is 0.33%.
[0072] Example 6
[0073] The coke powder is screened to obtain coke powder with a particle size of less than or equal to 4 mm, a volatile matter of 10.32%, and a moisture content of 5.80%.
[0074] Preparation of the mixture: adding asphalt binder, non-asphalt binder and water containing surfactant to the coke powder, and stirring evenly in a kneading pot to obtain the mixture. Among them, the softening point of the asphalt binder is 92°C, the coking value is 46.12%, the particle size is less than 2 mm, and the weight ratio of the asphalt binder to the dry basis coke powder is 0.10; the non-asphalt binder is sesbania gum, and the weight ratio of the non-asphalt binder to the dry basis coke powder is 0.022; the water containing the surfactant and the original water in the coke powder constitute the total water, and the weight ratio of the total water to the dry basis coke powder is 0.11; the weight ratio of the surfactant to water in the water containing the surfactant is 0.003, and the surfactant is Peregal O-30.
[0075] The mixed material is pressed on a double-roll forming machine with a linear pressure ratio of 0.2 t / cm. After pressing, a molded coke green block is obtained. The drop strength of the molded coke green block is 76.71%. The ambient temperature for stirring and pressing is 2°C.
[0076] Calcination of coke blocks: calcine the coke blocks at a maximum temperature of 1200°C to obtain coke blocks. The true density of coke blocks is 2.05 g·cm -3 , particle stability is 72.65%, powder resistivity is 517μΩ·m, and ash content is 0.35%.
[0077] Comparative Example 1-1
[0078] This comparative example is a comparative example of Example 1. Except that the non-asphalt binder is bentonite, other conditions are the same as those of Example 1. The drop strength of the prepared coke lump is 73.51%, and the true density of the calcined coke is 2.07 g·cm -3 , particle stability is 54.96%, powder resistivity is 539μΩ·m, and ash content is 2.96%.
[0079] Comparative Example 1-2
[0080] This comparative example is also a comparative example of Example 1. Except that the weight ratio of the non-asphalt binder to the dry basis powdered coke is 0.01, other conditions are the same as those of Example 1. The drop strength of the prepared coke lump is 37.50%, and the true density of the calcined coke is 2.06 g·cm -3 , particle stability is 71.59%, powder resistivity is 510μΩ·m, and ash content is 0.25%.
[0081] Comparative Example 2
[0082] This comparative example is a comparative example of Example 2. Except that no surfactant is used, other conditions are the same as those of Example 2. The drop strength of the prepared coke lump is 70.39%, and the true density of the calcined coke is 2.06 g·cm -3, particle stability is 77.61%, powder resistivity is 499μΩ·m, and ash content is 0.30%.
[0083] Comparative Example 3
[0084] This comparative example is a comparative example of Example 3. Except that calcined petroleum coke powder is used instead of petroleum coke powder, and there are differences in the indicators between calcined petroleum coke powder and petroleum coke powder, other conditions are the same as those of Example 3. The particle size of calcined petroleum coke powder is less than 1 mm, the volatile matter is 0.51%, and the moisture content is 0.22%. The drop strength of the prepared coke block is 80.27%, and the true density of the calcined coke is 2.07 g·cm -3 , particle stability is 30.63%, powder resistivity is 493μΩ·m, and ash content is 0.39%.
[0085] Comparative Example 4
[0086] This comparative example is a comparative example of Example 4. Except that the weight ratio of total water content to dry basis powdered coke is 0.05, other conditions are the same as those of Example 4. The drop strength of the prepared green coke block is 26.57%, and the true density of the calcined coke is 2.04 g·cm -3 , particle stability is 65.17%, powder resistivity is 541μΩ·m, and ash content is 0.23%.
[0087] The indicators of the green coke and calcined coke in the examples and comparative examples are shown in Table 1.
[0088] Table 1 Indexes of green coke and calcined coke
[0089]
[0090]
[0091] It can be seen from the results of the embodiments and comparative examples that the green coke blocks prepared by the method provided in the embodiments of the present disclosure have high drop strength, the strength of the coke after calcination is high, and the ash content and other indicators are good.
[0092] In a second aspect of the present disclosure, there is provided a shaped coke, which is made by the above-mentioned petroleum coke powder molding method.
[0093] In the present disclosure, the terms "first", "second", and "third" are used for descriptive purposes only and are not to be understood as indicating or implying relative importance; the term "plurality" refers to two or more, unless otherwise expressly defined. The terms "installed", "connected", "connected", "fixed", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; "connected" can be a direct connection or an indirect connection through an intermediate medium. For those of ordinary skill in the art, the specific meanings of the above terms in the present disclosure can be understood according to the specific circumstances.
[0094] In the description of the present disclosure, it is necessary to understand that the directions or positional relationships indicated by the terms "up", "down", "left", "right", "front", "back", etc. are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present disclosure and simplifying the description, rather than indicating or implying that the device or unit referred to must have a specific direction, be constructed and operated in a specific orientation, and therefore, should not be understood as a limitation on the present disclosure.
[0095] In the description of this specification, the description of the terms "one embodiment", "some embodiments", "specific embodiments", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present disclosure. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0096] The above are only preferred embodiments of the present disclosure and are not intended to limit the present disclosure. For those skilled in the art, the present disclosure may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present disclosure shall be included in the protection scope of the present disclosure.
Claims
1. A method for forming petroleum coke powder, characterized in that: include: Screening of fine coke, screening petroleum coke to obtain fine coke; Mixture preparation, adding an asphalt binder, a non-asphalt binder and water containing a surfactant to the powdered coke to obtain a mixture; Pressing the mixture into a mold, pressing the mixture into a mold on a molding machine to obtain molded coke green blocks; The molded coke block is calcined, and the molded coke green block is calcined to obtain molded coke.
2. The method for forming petroleum coke powder according to claim 1, characterized in that: In the step of screening the powdered coke, the particle size of the powdered coke is less than or equal to 5 mm, the volatile matter of the powdered coke is 7% to 13%, and the moisture content of the powdered coke is 0.1% to 9%.
3. The method for forming petroleum coke powder according to claim 1, characterized in that: The weight ratio of the asphalt binder to dry basis powdered coke is 0.03 to 0.
13.
4. The method for forming petroleum coke powder according to claim 1, characterized in that: The particle size of the asphalt binder is less than 2 mm, and the softening point of the asphalt binder is 90° C. to 150° C., and the coking value is 40% to 65%.
5. The method for forming petroleum coke powder according to claim 1, characterized in that: The forming machine is configured as a double-roll forming machine, and a linear pressure ratio of the double-roll forming machine is configured to be 0.2 to 1.5 t / cm.
6. The method for forming petroleum coke powder according to claim 1, characterized in that: The non-asphalt binder is guar gum, sesbania gum or hydroxypropyl methylcellulose.
7. The method for forming petroleum coke powder according to claim 1, characterized in that: The weight ratio of the non-asphalt binder to the dry basis coke powder is 0.02 to 0.
03.
8. The method for forming petroleum coke powder according to claim 1, characterized in that: The water containing the surfactant and the original water in the coke powder constitute total water, and the weight ratio of the total water to the coke powder is 0.10 to 0.
14.
9. The method for forming petroleum coke powder according to claim 1, characterized in that: In the calcining step of the shaped coke block, the temperature is set to 1100°C to 1300°C.
10. A shaped coke, characterized in that: The petroleum coke powder is produced by the molding method of any one of claims 1 to 9.
Citation Information
Cited By
Forming process of calcined powdery petroleum coke
CN120696179A